IMPLEMENTASI PROGRAM PKPU ( POS KEADILAN PEDULI UMAT) HUMAN INITIATIVE DALAM MEMBANTU PENGUNGSI ROHINGYA DI BANGLADESH - Rahmi Trirosa; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to describe the implementation of the PKPU Human Initiative program in helping the Rohingya humanitarian crisis in Bangladesh. The Rohingya humanitarian crisis that occurred because of conflict that occurred involving the Rohingya and Rakhine ethnic groups due to the Myanmar government's discrimination against the Rohingya ethnic group causing the Rohingya people to decide to leave Myanmar and flee to various countries, one of them Bangladesh. This research aims to find out the programs of PKPU Human Initiative in helping Rohingya humanitarian crisis in BangladeshThe research method used by the author is a qualitative method with primary data collection techniques through interviews and secondary data collection with library research. This research was developed based on the perspective of pluralism perspectives such as Robert O. Kohane, Joseph, S. Nye, Mattew Paterson and Cristian Reus-smit supported by international organizational theory by Leroy Bennet, and using the level of group analysis by David Singer (PKPU Human Initiative) as the main actor in international relations.The results showed that the role of PKPU Human Initiative as a humanitarian agency had carried out its function well, namely by implementing a program called